2008
DOI: 10.1002/jemt.20622
|View full text |Cite
|
Sign up to set email alerts
|

Assembling and imaging of his‐tag green fluorescent protein on mica surfaces studied by atomic force microscopy and fluorescence microscopy

Abstract: The adsorption of his-tag green fluorescent protein (GFPH(6)) onto the mica surfaces has been studied by atomic force microscopy (AFM) and laser confocal fluorescence microscopy. By controlling the adsorption conditions, separated single GFPH(6) and GFPH(6) monolayer can be adsorbed and formed on mica surfaces. In present experiments, based on the AFM measurement, we found that the adsorbed GFPH(6) was bound on the mica surface with its beta-sheets. The formed GFPH(6) monolayer on mica surfaces was flat, unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…The actual dimension of HSA should be less than these values due to the well‐known broadening effect caused by the finite probe tip radius in AFM imaging. The actual dimension of HSA can be estimated by a previously proposed formula to deconvolute the tip effects (Liu et al ., ). The calculated length of HSA after deconvolution is 12.6 nm and the width is 6.5 nm when the AFM tip radius assumed to be 10 nm.…”
Section: Resultsmentioning
confidence: 97%
“…The actual dimension of HSA should be less than these values due to the well‐known broadening effect caused by the finite probe tip radius in AFM imaging. The actual dimension of HSA can be estimated by a previously proposed formula to deconvolute the tip effects (Liu et al ., ). The calculated length of HSA after deconvolution is 12.6 nm and the width is 6.5 nm when the AFM tip radius assumed to be 10 nm.…”
Section: Resultsmentioning
confidence: 97%
“…When the size of the observed samples are equivalent to or smaller than the curvature radius of AFM tip, the well-known broadening effects arise (Bustamante et al 1992), which induced the observed length and width to be larger than its true values. This phenomenon has been verified in green fluorescent protein imaging by AFM in liquid (Liu et al 2008). Unfortunately, the central DNA-binding pore of TOPO I cannot be The observed longest part of a TOPO I was measured as its length; the height and the width was measured at the vertical center according to its length, and the width was measured at half maximum height.…”
Section: Resultsmentioning
confidence: 97%
“…TOPO I monolayer can be formed by adsorbing high concentration of TOPO I on mica surface. The TOPO I monolayer on mica surface has very stable characteristics, and may have some potential applications (Liu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations